The continual threat of influenza virus infections at the human–animal interface: What is new from a one health perspective?. Issue 1 (7th September 2018) - Bailey, Emily S; Choi, Jessica Y; Fieldhouse, Jane K; Borkenhagen, Laura K; Zemke, Juliana; Zhang, Dingmei; Gray, Gregory C
Abstract: This year, in 2018, we mark 100 years since the 1918 influenza pandemic. In the last 100 years, we have expanded our knowledge of public health and increased our ability to detect and prevent influenza; however, we still face challenges resulting from these continually evolving viruses. Today, it is clear that influenza viruses have multiple animal reservoirs (domestic and wild), making infection prevention in humans especially difficult to achieve. With this report, we summarize new knowledge regarding influenza A, B, C and D viruses and their control. We also introduce how a multi-disciplinary One Health approach is necessary to mitigate these threats.